2011
DOI: 10.4317/medoral.16.e541
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and ventilatory changes during implant surgery with intravenous conscious sedation

Abstract: Purpose: This study was conducted to determine the hemodynamic and ventilatory changes during implant surgery with intravenous conscious sedation, and whether preoperative anxiety, gender or age influence these parameters. Patients and Methods: A prospective study carried out between May 2004 and February 2007, on 102 patients treated with dental implants under local anesthesia and conscious intravenous sedation. Patients completed a questionnaire prior to surgery to evaluate preoperative dental anxiety using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Concerning respiratory parameters, the current case series found an average intraoperative pulse oxygenation drop of 2.02%. Similarly, intraoperative pulse oxygenation dropped an average of 2.05% in the study by González‐Lemonnier et al 18 These findings are in agreement with a much larger study by Viljoen et al, 19 who evaluated oxygen saturation levels in 3,500 dental conscious‐sedation cases. The results of their study found that some patients had pulse oxygenation values drop below 94% and concluded that “a single operator/sedationist, supported by a well‐trained team of nurses, can consistently maintain safe oxygen saturation levels.” 19 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Concerning respiratory parameters, the current case series found an average intraoperative pulse oxygenation drop of 2.02%. Similarly, intraoperative pulse oxygenation dropped an average of 2.05% in the study by González‐Lemonnier et al 18 These findings are in agreement with a much larger study by Viljoen et al, 19 who evaluated oxygen saturation levels in 3,500 dental conscious‐sedation cases. The results of their study found that some patients had pulse oxygenation values drop below 94% and concluded that “a single operator/sedationist, supported by a well‐trained team of nurses, can consistently maintain safe oxygen saturation levels.” 19 …”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, whereas a heart rate reduction of 9.69% was found in the present procedures, Win et al 6 reported a 10.81% increase in heart rate. A 2011 study by González‐Lemonnier et al 18 evaluating hemodynamic and respiratory changes during dental implant surgery with conscious sedation found that systolic and diastolic blood pressures dropped 7.1% and 11.4%, respectively, while heart rate increased 7.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in blood pressure (BP) is common even in healthy subjects. Research groups have studied the changes in blood pressure, body temperature, oxygen saturation level and heart rate in different stages of the dental surgery [1][2][3]. Gedik et al [2] has reported the factors such as patient age, gender, education and volume of anesthetic drug used are strong determinants of the extent of changes in the heart rate, blood pressure and temperature before and after oral surgery.…”
Section: Introductionmentioning
confidence: 98%
“…González-Lemonnier et al [6] monitored hemodynamic and ventilator changes during implant surgery with intravenous conscious sedation using midazolam and fentanyl. They reported that the highest systolic and diastolic BPs were reported during incision and raising of the mucoperiosteal flap, whereas the lowest SpO 2 was recorded at the local anesthetic injection.…”
Section: Introductionmentioning
confidence: 99%